2014
DOI: 10.1371/journal.pone.0091000
|View full text |Cite
|
Sign up to set email alerts
|

RAN Nucleo-Cytoplasmic Transport and Mitotic Spindle Assembly Partners XPO7 and TPX2 Are New Prognostic Biomarkers in Serous Epithelial Ovarian Cancer

Abstract: PurposeEpithelial ovarian cancer has the highest mortality rate of all gynecological malignancies. We have shown that high RAN expression strongly correlates with high-grade and poor patient survival in epithelial ovarian cancer. However, as RAN is a small GTPase involved in two main biological functions, nucleo-cytoplasmic transport and mitosis, it is still unknown which of these functions associate with poor prognosis.MethodsTo examine the biomarker value of RAN network components in serous epithelial ovaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 50 publications
1
43
0
Order By: Relevance
“…Such results have revealed the correlation between TPX2 and the tumorigenesis of cancer. In addition, it has been demonstrated that the overexpression of TPX2 serves an important role in the progression and invasion of human malignancies (21), and that its expression is associated with the aggressiveness of ovarian cancer (22). Previous studies have reported that TPX2 is involved in cell proliferation and associated with poor prognosis in patients with esophageal cell carcinoma (23,24), supporting the hypothesis that TPX2 functions as a tumor promoter in this particular type of cancer.…”
Section: Introductionmentioning
confidence: 80%
“…Such results have revealed the correlation between TPX2 and the tumorigenesis of cancer. In addition, it has been demonstrated that the overexpression of TPX2 serves an important role in the progression and invasion of human malignancies (21), and that its expression is associated with the aggressiveness of ovarian cancer (22). Previous studies have reported that TPX2 is involved in cell proliferation and associated with poor prognosis in patients with esophageal cell carcinoma (23,24), supporting the hypothesis that TPX2 functions as a tumor promoter in this particular type of cancer.…”
Section: Introductionmentioning
confidence: 80%
“…In recent years, a connection between TPX2 and initiation, progression and prognosis of malignant tumor is becoming a focus of researches [15] . Previous studies showed that abnormally high expression of TPX2 has been confirmed in many tumor tissues [16,17] . TPX2 can upregulate expression of matrix metalloproteinases (MMP) family through activating PI3K/Akt pathway.…”
Section: Introductionmentioning
confidence: 94%
“…It has been found that elevated expression of TPX2 promotes tumor growth in pancreatic cancer [39] . Also, high levels of TPX2 expression are correlated with the aggressiveness of ovarian and salivary gland cancers [17,40] .…”
mentioning
confidence: 99%
“…Tumors were fixed in formaldehyde (3.7%, v/v) and embedded in paraffin, or lysed in RIPA buffer, and then processed for IHC (two slices/ tumor) or Western blotting, respectively (31,32). For pY 418 Src and CD31 immunofluorescence, paraffin-embedded tumor slices were dewaxed, subjected to antigen retrieval, and incubated with primary antibodies using the BenchMark XT automated stainer (Ventana Medical System Inc.; ref.…”
Section: Tumor Growth and Metastasis Assaymentioning
confidence: 99%
“…For pY 418 Src and CD31 immunofluorescence, paraffin-embedded tumor slices were dewaxed, subjected to antigen retrieval, and incubated with primary antibodies using the BenchMark XT automated stainer (Ventana Medical System Inc.; ref. 31). Afterward, on the bench, tumor slices were incubated with secondary antibodies as described above ("In vivo VEGF stimulation" section).…”
Section: Tumor Growth and Metastasis Assaymentioning
confidence: 99%